Penyuluhan dan Video Demonstrasi Pengolahan MP-ASI Untuk Mencegah Stunting di Desa Pallawa Rukka Kecamatan Ulaweng Kabupaten Bone - St. Malka; Mutmainnah Mutmainnah; Musni Musni; Desy Heryana (Pusat Riset dan Inovasi Nasional, 2024)
Stunting is a problem of insufficient nutritional intake during the first 1000 days of a child's life, causing failure to grow and develop in children. Stunted children will generally look the same as other normal children, but the differences will be clearly visible when the child is 2 years old, which is characterized by a height that is not appropriate for children his age, and his face looks older than his age. After identification, 50% of mothers who have babies and toddlers are not aware of stunting. The aim of this service is to provide health education to mothers of babies and toddlers through counseling and video demonstrations of MP-ASI processing to increase understanding as an effort to prevent stunting. The method of service carried out is counseling about stunting and a video demonstration of the MP-ASI innovation, namely making vegetable chicken sempol. The results of the implementation evaluation before being given counseling were in the sufficient knowledge category (28.6%) and after being given counseling it was (85.7%) meaning that the counseling was successful.